Fantasies of Race: A Transatlantic Approach to Class and Sexuality in Emilia Pardo Bazán's La Tribuna1. Issue 5 (June 2015) - MATEOS, ANA
Abstract : In this essay I propose that the concept of race, especially within a transatlantic context, is fundamental for understanding the interdependent discourses of class and sexuality in Emilia Pardo Bazán's La Tribuna (1883). In this way, I rethink the novel's notorious oscillation between the denunciation of patriarchy and bourgeois hegemony on the one hand, and the portrayal of the working class and Amparo's sexuality as social threats on the other. Both sides of this tension are articulated through racial discourses in the representation of Amparo. This approach sheds light on the novel's silence regarding the question of the abolition of slavery in Cuba, despite conjuring the figure of the slave to highlight Amparo's exploitation.